Developing a prism qualification test to ensure adequate splitting resistance in pretensioned concrete railroad ties - Savic, Adrijana (Kansas State University, 2019)
This research represents a successful step in the development of a qualification test to ensure adequate splitting resistance in pre-tensioned concrete railroad ties. The research evaluated the influence of the edge distance, compressive strength of concrete and the type of wire indentation on bond performance between prestressing steel and concrete when using different concrete mixtures. The bond between prestressing wires and concrete is crucial for transferring the stresses between the two materials in a pretensioned concrete member. Furthermore, bond can be affected by such variables as edge distance, type of prestressing (typically indented) wire used, compressive (release) strength of the concrete, and concrete mixture. A key objective of the current research is to find the best parameters for prestressed concrete ties to avoid longitudinal splitting in track. This work presents the background work for the development of a testing procedure to eliminate the combination of parameters that result in splitting. The objective is to develop a qualification test procedure to proof-test new or existing combinations of prestressing wire, concrete mix, and compressive strength of concrete and edge distance to ensure a reliable result. This is particularly crucial in the concrete railroad crosstie industry, where incompatible conditions can result in longitudinal splitting cracks and even tie failure. The goal is to develop a qualification test with the capability to readily identify compatible wire/concrete designs “in-plant” before the ties are manufactured, thereby eliminating the likelihood that defectively manufactured ties will lead to in-track tie failures due to splitting. A study was conducted at Kansas State University to understand the effect of edge distance, indent type, the compressive release strength and concrete mixture on the longitudinal splitting behavior between steel and concrete. For the experimental testing three prisms with different cross sections were cast simultaneously in series. The tests presented here were conducted on pre-tensioned concrete prisms cast in steel frames. Four prestressing wires were symmetrically embedded into each concrete prism, resulting in a horizontal and vertical wire spacing of 2.0 in. The prisms were 59.5 in long with square cross sections. The first prism was 3.5 x 3.5 in with cover ¾ in, the second was 3.25 x 3 .25 in with cover ⅝ in and the third prism in series was 3.0 x 3.0 in with cover ½ in. All prestressing wires used in these initial tests were 5.32 mm (0.21 in) diameter and had different indentation types. The indent pattern variations of the wires included spiral, classical chevron shape, and the extreme case of smooth wire with no indentions. The wires were initially tensioned to 7000 lbs. and then gradually de-tensioned after reaching the desired compressive strength. The different compressive (release strength) strength levels tested included 3500 psi, 4500 psi, 6000 psi and extreme case of 12000 psi for one wire type. Three different concrete mixtures with a water-to-cementitious (w/c) ratio 0.32 were used for all castings except one test where a 0.38 w/c ratio was used. For compressive release strength 12000 psi a 0.26 w/c ratio was used, and desired strength was achieved after 6 days. Concrete-to-steel reinforcement ratios and mechanical properties of test prisms were representative of actual prestressed concrete crossties used in the railroad industry.
Keywords: Prestressed concrete; Railroad ties; Arema manual; Concrete cover; Wire; Concrete mixtures